Agricultural Production and Agricultural Employment Rate in South Africa: Time Series Analysis Approach - Ramakgasha, Molobe Joyce; Thaba, Tshephi Kingsley; Rudzani, Nengovhela (International Journal of Economics and Financial Issues, 2024)
South Africa’s agricultural sector, despite facing high unemployment, is acknowledged for creating job opportunities. However, there is concern that the sector’s adoption of technology-intensive methods may not necessarily lead to increased employment. The study aims to analyze the intricate relationship between agricultural output and employment in South Africa using time series analysis. This research employed a Vector Autoregressive (VAR) model to evaluate the link between agricultural production and the rate of agricultural employment in South Africa spanning from 1990 to 2022. The findings indicate that both variables passed levels and became stationarity at the first difference when employing ADF, and a long-term equilibrium relationship between the variables was observed using Johansen cointegration test. Over the short term, there was a significant positive correlation among agricultural production and the agricultural employment rate evidenced from ECT coefficient of 0.139 value. The results of the Granger causality tests indicated unidirectional relationship that agricultural employment Granger-causes agricultural production, signifying that agricultural employment can be used to predict the growth of agricultural production. Study recommended that policies which promote injection of funds to improve production in the agriculture sector needs to be prioritized to maintain and improve employment opportunities.